300°C operation of normally‐off AlGaN/GaN MOSFET with low leakage current and high on/off current ratio. Issue 4 (1st February 2014) - Xu, Zhe; Wang, Jinyan; Cai, Yong; Liu, Jingqian; Yang, Zhen; Li, Xiaoping; Wang, Maojun; Yang, Zhenchuang; Xie, Bin; Yu, Min; Wu, Wengang; Ma, Xiaohua; et al.
Abstract : 300°C operation of a normally‐off AlGaN/GaN metal‐oxide semiconductor field‐effect transistor (MOSFET) is successfully demonstrated, which is fabricated using a self‐terminating gate recess etching technique. At 300°C, by employing a 15 nm‐thick Al2 O3 as the gate dielectric deposited by atomic layer deposition, the fabricated normally‐off MOSFET exhibits a threshold voltage ( V th ) of 3.2 V, a low off‐state leakage current of ∼10 −7 A/mm and a low forward gate leakage current of ∼10 −7 A/mm. Thus, a high on/off current ratio of ∼ 10 6 is obtained. Furthermore, the normally‐off MOSFET also exhibits small variations in terms of its V th from room temperature to 300°C with a maximum relative variation of 6.7% in a such temperature range. These results make this normally‐off AlGaN/GaN MOSFET very promising for high‐temperature digital electronics.